Distinctive roles of RhoA and RhoC in glioma cell motility, invasion, and invadopodia assembly. (c2018) - Dennaoui, Rayane (2018)
Malignant gliomas remain a medical concern in oncology due to their high morbidity rates and their aggressive behavior in the invasion of normal brain parenchyma. It has been a challenge to cure these types of brain tumors owing to the importance of the brain in regulating a plethora of human physiological functions, chemotherapy resistance, and inefficient surgical resection. Cell motility and invasion are patterns of glioma spreading and are multifaceted processes involving dynamic changes in the actin cytoskeleton. Major regulators that orchestrate actin reorganization and migration are members of the Rho family of GTPases. In this study, we investigate the contribution of two structurally similar Rho proteins, RhoA and RhoC, in glioma migration and invasion. One of our objectives was to explore the effects of both RhoA and RhoC on two- dimensional motility. Our data suggest that both proteins are positive regulators and enhancers of cell migration, adhesion to the extracellular matrix, and protrusion formation through the regulation of actin cytoskeletal dynamics. Another objective for the study was to study the differential roles of RhoA and RhoC in invasion and invadopodia assembly. We have found that RhoC is the main driver of the process in astrocytomas. In addition, we investigated possible cross-talks between RhoA, RhoC, Cdc42, and Rac1. Our data suggest that RhoA and RhoC downregulate both Rac1 and Cdc42 in order to achieve their roles in motility and invasion.